Prinsip-Prinsip Manajemen Kinerja - Aswaruddin Aswaruddin; Hasana Fadilla; Puspita Dewi; Renilda Putri; Alfie Ridho; Fajar Baihaq’qi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Performance is the result of work and also an assessment of the work of someone who is involved in the world of work in an agency. Therefore, performance also requires management, so that the results obtained or the performance of workers or employees can achieve the results aimed at by the company. These principles include measurement, development, communication and incentives aimed at improving performance effectively and efficiently. Using this research is a qualitative research approach with a descriptive method approach. The overall goal of performance management is to build a high-performance culture in which individuals and teams are accountable for the continuous improvement of business processes and for their skills and contributions within the framework provided by their own effective leadership. The main goal is to focus people on doing the right thing by achieving goal clarity.